Inclusive Peacebuilding through Nahdlatul Ulama in Local Conflict Resolution - Rista Talib; Aldy Nurdiansyah (NAHNU: Journal of Nahdlatul Ulama and Contemporary Islamic Studies, 2026)
This study examines the dynamics of socio-political conflict at the local level in Makassar and highlights the strategic role of Nahdlatul Ulama in constructing sustainable peace. Using a qualitative descriptive approach based on literature review and document analysis of scholarly publications, organizational documents, and research reports published mainly between 2021–2026. The findings indicate that socio-political conflicts tend to manifest in latent forms such as polarization, fragmentation, and identity-based tensions. Nahdlatul Ulama plays a significant role through deliberation-based dialogic mediation, inclusive dialogue, participatory decision-making, and trust-building among conflicting groups. In addition, the implementation of religious moderation through religious activities, education, and preaching strengthens social harmony and prevents conflict escalation. The study also highlights digital transformation as both an opportunity and a challenge in disseminating peace values. Overall, the integration of dialogic approaches, moderation values, and digital adaptation is essential for achieving sustainable peace at the local level.   Studi ini meneliti dinamika konflik sosial-politik di tingkat lokal di Makassar dan menyoroti peran strategis Nahdlatul Ulama dalam membangun perdamaian berkelanjutan. Menggunakan pendekatan deskriptif kualitatif berdasarkan tinjauan pustaka dan analisis dokumen publikasi ilmiah, dokumen organisasi, dan laporan penelitian yang diterbitkan terutama antara tahun 2021–2026. Temuan menunjukkan bahwa konflik sosial-politik cenderung bermanifestasi dalam bentuk laten seperti polarisasi, fragmentasi, dan ketegangan berbasis identitas. Nahdlatul Ulama memainkan peran penting melalui mediasi dialogis berbasis musyawarah, dialog inklusif, pengambilan keputusan partisipatif, dan pembangunan kepercayaan di antara kelompok-kelompok yang berkonflik. Selain itu, implementasi moderasi agama melalui kegiatan keagamaan, pendidikan, dan dakwah memperkuat harmoni sosial dan mencegah eskalasi konflik. Studi ini juga menyoroti transformasi digital sebagai peluang sekaligus tantangan dalam menyebarkan nilai-nilai perdamaian. Secara keseluruhan, integrasi pendekatan dialogis, nilai-nilai moderasi, dan adaptasi digital sangat penting untuk mencapai perdamaian berkelanjutan di tingkat lokal.